CULTURAL DA'WAH APPROACH IN THE AKKAWARU TRADITIONAL CEREMONY TRADITION IN GANTARANGKEKE, BANTAENG REGENCY - St. Nasriah; Audah Mannan (TASAMUH : Jurnal Komunikasi dan Pengembangan Masyarakat Islam, 2025)
This study aims to analyze the cultural da‘wah approach embedded in the traditional Akkawaru ceremony in Gantarangkeke District, Bantaeng Regency, South Sulawesi. Akkawaru represents a form of local wisdom of the Bugis–Makassar community that contains spiritual, social, and religious values that are still preserved today. This research employs a qualitative approach with a descriptive-ethnographic design. Data were collected through participant observation, in-depth interviews, and documentation involving 6 informants, consisting of traditional leaders, religious figures, community leaders, ritual practitioners, and local residents directly involved in the Akkawaru ceremony. Informants were selected using purposive sampling. Data analysis was conducted using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure data validity. The findings reveal that Akkawaru functions not merely as a customary ritual but also as a medium of da‘wah conveying Islamic values such as gratitude to God, social solidarity, communal harmony, and respect for all of God’s creation. The cultural da‘wah approach within the Akkawaru tradition has proven effective in delivering Islamic teachings in a contextual, peaceful, and inclusive manner, while also strengthening religious moderation and social cohesion within the local community.